Synthesis, structure and electrochemical properties of diiron S-(−)-1-Phenylethylazadithiolate complexes. (24th November 2017) - Li, Yu-Long; He, Jiao; Wei, Juan; Wei, Jian; Mu, Chao; Wu, Yu; Xie, Bin; Zou, Li-Ke; Wang, Zheng; Wu, Mei-Li; Li, Han-Min; Gao, Fan; et al.
Graphical abstract: Four new diiron S-(−)-1-phenylethylazadithiolate complexes1 –4 have been prepared and fully characterized by elemental analysis and IR, NMR ( 1 H, 13 C, 31 P) spectroscopies, and for1, 2 and4 by X-ray crystallography. Complexes1 and2 were found to be catalysts for hydrogen production under electrochemical conditions. According to the electrochemical observations, a possible catalytic EECC or ECEC mechanism was proposed. Abstract: A novel diiron S-(−)-1-phenylethylazadithiolate complex, Fe2 [( μ -SCH2 )2 NCH(CH3 )Ph](CO)6 (1 ), has been prepared by the condensation of Fe2 ( μ -SH)2 (CO)6, CH2 O and S-(−)-1-phenylethylamine. Furthermore, the reaction of complex1 and phosphine ligands (PPh3, P(C6 H4 -4-F)3, dppe) in the presence of the decarbonylation agent Me3 NO·2H2 O resulted in the formation of the phosphine-substituted diiron S-(−)-1-phenylethylazadithiolate complexes Fe2 [( μ -SCH2 )2 NCH(CH3 )Ph](CO)5 (PPh3 ) (2 ), Fe2 [( μ -SCH2 )2 NCH(CH3 )Ph](CO)5 [P(C6 H4 -4-F)3 ] (3 ) and Fe2 [( μ -SCH2 )2 NCH(CH3 )Ph](CO)5 2 (Ph2 PCH2 CH2 PPh2 ) (4 ). Complexes1 –4 have been fully characterized by elemental analysis, FTIR and NMR ( 1 H, 13 C, 31 P) spectroscopies, and for1, 2 and4 by X-ray crystallography. Moreover, complexes1 and2 were found to be catalysts for hydrogen production in the presence of acid under electrochemical conditions. According to the electrochemical observations, a possible catalytic mechanism for complexes1 and2 was proposed.